2011
DOI: 10.1007/s11270-011-0769-x
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry of Mercury Along a Soil Profile Compared to Other Elements and to the Parental Rock: Evidence of External Input

Abstract: The vertical distribution of mercury along a weathering profile derived from a diabase was compared to the main geochemical and mineralogical characteristics of the soil and its parental rock. The sampling site was in a metropolitan area, nearby to an active quarry and relatively close to an industrial park.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 55 publications
3
18
0
2
Order By: Relevance
“…Hg concentrations across the six weathering profiles (0.4 to 282 ng/g) were comparable to the range of values reported by previous studies on nonpoint source polluted forested soils in North America (e.g., Obrist et al, 2009;Obrist et al, 2011;Richardson et al, 2013;Smith et al, 2013), tropical South America (e.g., Fiorentino et al, 2011), temperate and subtropical China (Luo et al, 2014), and temperate and Mediterranean Europe (Peña-Rodríguez et al, 2012;Schwesig & Matzner, 2001). Furthermore, Hg concentrations were generally lower than those reported in point-source polluted areas such as soils near artisanal gold mining (e.g., 70-420 ng/g of soils in French Guyana studied by Guedron et al, 2009) and soils near metropolitan areas in China (e.g., 110-2178 ng/g in Shi et al, 2013).…”
Section: Mercury Concentrations and Inventories In Weathering Profilessupporting
confidence: 87%
“…Hg concentrations across the six weathering profiles (0.4 to 282 ng/g) were comparable to the range of values reported by previous studies on nonpoint source polluted forested soils in North America (e.g., Obrist et al, 2009;Obrist et al, 2011;Richardson et al, 2013;Smith et al, 2013), tropical South America (e.g., Fiorentino et al, 2011), temperate and subtropical China (Luo et al, 2014), and temperate and Mediterranean Europe (Peña-Rodríguez et al, 2012;Schwesig & Matzner, 2001). Furthermore, Hg concentrations were generally lower than those reported in point-source polluted areas such as soils near artisanal gold mining (e.g., 70-420 ng/g of soils in French Guyana studied by Guedron et al, 2009) and soils near metropolitan areas in China (e.g., 110-2178 ng/g in Shi et al, 2013).…”
Section: Mercury Concentrations and Inventories In Weathering Profilessupporting
confidence: 87%
“…Mercury concentration in crustal rocks is still poorly defined, but a recent study on arc crustal rocks reported much lower Hg concentration (2.9 ± 2.6 ppb) [ Canil et al ., ] than most of our mineral soil samples. In addition, previous studies on Hg sources in soils using geochemical ratios also show that the dominant source of Hg in upper soils is from exogenic (i.e., atmospheric) inputs rather than from geogenic sources [ Grimaldi et al ., ; Fiorentino et al ., ; Peña‐Rodríguez et al ., ]. Note that the contribution of geogenic Hg may vary between sites.…”
Section: Resultsmentioning
confidence: 99%
“…The magmatic and metamorphic rocks making up the Guiana and Brazilian shields, which border the Amazon basin to the northeast and south, have low concentrations of Hg, ranging from 4 to 7 ng g -1 for granites, basalts and andesites in French Guiana (Guédron et al, 2006). These concentrations are lower than, or equal to, those obtained for rocks of a comparable nature found in Brazil (Fiorentino et al, 2011) and on other continents (Gao et al, 1998). Except for certain minerals, which are generally sulfur (S)-bearing (cinnabar: HgS), Mercury is present as impurities in the crystalline lattices of minerals (Andersson, 1979).…”
Section: Origins and Carrier Phases Of Mercury Accumulated In Soilsmentioning
confidence: 75%